WORKSHOP PENGEMBANGAN TIK : DIGITAL MARKETING PEMERINTAH DAERAH - Syaddam, Syaddam (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2024)
Digital marketing has become an important part of today's marketing strategy. Digital marketing is a technique for marketing products or services using digital media, such as social media, email marketing, websites, and SEO. The Community Service Activity held in May 2024 in the Ruang Imbaya Kantor Walikota Tarakan, aims to improve the understanding and ability of Tarakan City Government Official in implementing digital marketing strategies to support the government's digital transformation. Through a Workshop that includes the delivery of materials and discussion sessions, participants gain a deep understanding of the concepts, strategies, and techniques of digital marketing that can be utilized in local government environments to increase engagement and communication with the community. This activity also discusses the role of digital marketing in supporting Government Digital Transformation, the characteristics of digital transformation, and the objectives of digital marketing for government. The interactive discussion session allows participants to deepen their understanding of the material presented and share experiences related to using government applications and the obstacles faced. The results of this activity received enthusiasm from the participants, which in this case was shown from the interaction between participants and speakers in the discussion session. This indicates that this activity can be an effective means to improve the knowledge and abilities of Government Official in utilizing digital marketing to support digital transformation in local government environments.